2018
DOI: 10.1111/ane.12924
|View full text |Cite
|
Sign up to set email alerts
|

The clinical features in Chinese patients with PRNP D178N mutation

Abstract: Unlike the western populations, the diverse phenotypical presentations of D178N mutants were not simply determined by the 129 genotypes in Chinese. The underlying modifying factors for phenotypical variations warrant further investigations. For those with atypical clinical and imaging features, genetic testing was important for final diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…By providing evidence for the existence of two distinct prions associated with the pathological variability of patients with FFI, our study helps to explain unresolved issues in FFI. It has been reported that there are patients with FFI who exhibit multiple and mixed clinical symptoms of both FFI and Creutzfeldt–Jakob disease ( Zarranz et al , 2005 ; Synofzik et al , 2009 ; Chen et al , 2018 ) and that patients with FFI also show significant neuropathological phenotypic variability ( Manetto et al , 1992 ; McLean et al , 1997 ; Yamashita et al , 2001 ; Sasaki et al , 2005 ). The genotype at codon 129 in the non-mutated allele is known to affect the clinical and pathological features in FFI.…”
Section: Discussionmentioning
confidence: 99%
“…By providing evidence for the existence of two distinct prions associated with the pathological variability of patients with FFI, our study helps to explain unresolved issues in FFI. It has been reported that there are patients with FFI who exhibit multiple and mixed clinical symptoms of both FFI and Creutzfeldt–Jakob disease ( Zarranz et al , 2005 ; Synofzik et al , 2009 ; Chen et al , 2018 ) and that patients with FFI also show significant neuropathological phenotypic variability ( Manetto et al , 1992 ; McLean et al , 1997 ; Yamashita et al , 2001 ; Sasaki et al , 2005 ). The genotype at codon 129 in the non-mutated allele is known to affect the clinical and pathological features in FFI.…”
Section: Discussionmentioning
confidence: 99%
“…insomnia and valine with familial CJD, 2 although this association may not be universal. 33,34 In our cohort, 28 patients could be unambiguously identified as D178N_cis129M and 5 patients as D178N_cis129V. No differences in mean antibody reactivity were seen between those 2 groups (table 4).…”
Section: Description Of the Cohortmentioning
confidence: 64%
“…None of the polymorphisms significantly altered autoantibody response to PrP C in a post hoc analysis ( table 4). In D178N carriers, the clinical phenotype was suggested to be dependent on the PRNP cis c.129 polymorphism: methionine was associated with FFI and valine with fCJD 2 , although this association may not be universal 33, 34 . In our cohort, n = 28 patients could be unambiguously identified as D178N_ cis 129M and n = 5 patients as D178N_ cis 129V.…”
Section: Resultsmentioning
confidence: 99%